2014
DOI: 10.1371/journal.pone.0084556
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Survey and Expression Analysis of the Putative Non-Specific Lipid Transfer Proteins in Brassica rapa L

Abstract: BackgroundPlant non-specific lipid transfer proteins (nsLtps) are small, basic proteins encoded by multigene families and have reported functions in many physiological processes such as mediating phospholipid transfer, defense reactions against phytopathogens, the adaptation of plants to various environmental conditions, and sexual reproduction. To date, no genome-wide overview of the Brassica rapa nsLtp (BrnsLtp) gene family has been performed. Therefore, as the first step and as a helpful strategy to elucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
71
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 100 publications
6
71
2
Order By: Relevance
“…In addition, G. arboreum lost all the Type III and Type IX nsLTPs (Fig. S2), suggesting that the evolution of plants not only involves gene retentions, but also is accompanied by gene losses and mutations428. Meanwhile, the proportion of nsLTPs in each subfamily indicated that Type I seemed to have contracted while Type VIII expanded in G. hirsutum compared with its diploid progenitors (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In addition, G. arboreum lost all the Type III and Type IX nsLTPs (Fig. S2), suggesting that the evolution of plants not only involves gene retentions, but also is accompanied by gene losses and mutations428. Meanwhile, the proportion of nsLTPs in each subfamily indicated that Type I seemed to have contracted while Type VIII expanded in G. hirsutum compared with its diploid progenitors (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…These peptides are structurally characterized by an eight cysteine motif (8 CM) backbone with the general form C-Xn-C-Xn-CC-CXC-Xn-C-Xn-C, and the cysteine residues are linked by four disulfide bonds to stabilize a tertiary structure of a hydrophobic cavity23. Moreover, almost all nsLTPs carry an N-terminal secretory signal peptide (21–27 amino acids in length) in their nascent polypeptides, indicating that they are secreted proteins24. In previous studies, plant nsLTPs have been identified to participate in a range of biological processes, including cuticular wax and cutin synthesis, biotic and abiotic stress resistance, plant signaling, seed maturation and sexual reproduction24.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Genome-wide analyses of gene superfamilies have been widely performed after the completion of numerous plant genome projects. For instance, numerous genome-wide studies of gene superfamilies have been performed in the diploid species, B. rapa and B. oleracea (Song et al, 2013; Duan et al, 2014; Li et al, 2014; Diehn et al, 2015; Lu et al, 2015). Several gene superfamilies have also been reported in the allotetraploid species B. napus (Sun et al, 2014; Raboanatahiry et al, 2015) However, a comprehensive analysis of the superfamily of genes underlying the flavonoid biosynthesis pathway in Brassica has not been reported to date.…”
Section: Discussionmentioning
confidence: 99%